Closing the gap: Nonviral TFAMoplex transfection boosted by bZIP domains compared to AAV-mediated transduction - Steffen Honrath; Miguel Heussi; Lukas Beckert; David Scherer; Roderick Y.H. Lim; Michael Burger; Jean-Christophe Leroux (Molecular Therapy: Nucleic Acids)
The TFAMoplex is a nanoparticulate gene delivery system based on the mitochondrial transcription factor A (TFAM) protein, which can be engineered with various functional domains to enhance plasmid DNA transfection. In this study, we aimed at improving the TFAMoplex system by incorporating basic leucine zipper (bZIP) domains, derived from the cyclic AMP (cAMP)-responsive element-binding protein (CREB), which are known to bind DNA upon dimerization. Additionally, we screened bZIP domains of other proteins (i.e., transcription regulator protein BACH1, cyclic AMP-dependent transcription factor ATF-3, and basic leucine zipper transcriptional factor ATF-like BATF) under challenging transfection conditions, identifying the bZIP domain of BACH1, bZIPBACH1, as particularly effective in enhancing the TFAMoplex performance, reducing the half-maximal effective concentration by more than 2-fold. We show that bZIP domains facilitate interactions with the cell membrane as single proteins and thus increase the cell association of TFAMoplexes. Finally, we compared the optimized bZIPBACH1-TFAMoplex to adeno-associated viruses (AAVs) regarding in vitro transfection efficiency and transgene expression levels. While AAVs achieved higher transfection efficiency based on the number of transfected cells, both the original and improved TFAMoplex constructs surpassed AAVs in transgene expression per cell.